Type analysis of Cymbella schubartii and two new Encyonopsis species (Bacillariophyceae) from southeastern Brazil - Wengrat, Simone; Marquardt, Gisele Carolina; Bicudo, Denise De Campos; Bicudo, Carlos Eduardo De Mattos; Wetzel, Carlos Eduardo; Ector, Luc (Phytotaxa, 2015)
The type material of Cymbella schubartii was studied in order to clarify the differences and similarities within the complex of Encyonopsis species observed in southeastern Brazilian water bodies. Detailed examination using light and scanning electron microscopy of modern populations led us to propose two new Encyonopsis species, which are here described in details. Morphometric analysis of the valve shape supported the separation of four species: Encyonopsis schubartii, E. difficilis, E. sanctipaulensis, sp. nov. and E. linensis, sp. nov. Additionally, Cymbella perpusilla var. moreirae is formally transferred to the genus Encyonopsis. Regarding their ecological preferences, these species were found in rivers and reservoirs, especially in oligotrophic and oligo-mesotrophic environments.